Antimalarial drugs reduce cytoadherence and rosetting Plasmodium falciparum. - Udomsangpetch, R; Pipitaporn, B; Krishna, S; Angus, B; Pukrittayakamee, S; Bates, I; Suputtamongkol, Y; Kyle, D; White, N (1996)
The in vivo and in vitro effects of antimalarials on cytoadherence and rosette formation were studied in 17 patients with severe and 46 with uncomplicated falciparum malaria. Cytoadherence was increased in severe malaria (P<.001). Artesunate and artemether were more potent than quinine in inhibiting both adherence properties. Artesunate was the most rapidly acting drug tested, producing >50% inhibition of both cytoadherence and rosetting in vivo and in vitro within 2 hr of drug exposure. Exposure to quinine for > or = to 4 h in vivo reduced rosetting by >50%, but not cytoadherence. Quinine did not reduce cytoadherence or rosetting significantly in vitro with exposure times of < or = to 8 h. These results suggest that artemisinin derivatives are more effective than quinine in preventing pathologic processes in parasitized erythrocytes that contribute to microvascular obstruction in severe malaria.